Christianity at the crossroads: the global church from the print revolution to the digital era - Hempton, David (Cambridge University Press, 2025)
Combining expansive storytelling with striking analysis of 'networks, nodes, and nuclei', David Hempton's new book explains major developments in global Christianity between two communication revolutions: print and the internet. His novel approach (replete with vivid metaphor - we read of wildflower gardens and fungi, of exploding fireworks sending sparks of possibility in all directions, and of forests with vast interconnected root systems hidden below our vision) allows him to look beyond institutional hierarchies, traverse national and denominational boundaries, and think more deeply about the underlying conditions promoting, or resisting, adaptation and change. It also enables him to explore the crossroads, or junction boxes, where individuals and ideas encountered different traditions and from which something fresh and dynamic emerged. Cogently addressing the rise of empires, transformation of gender relations, and demographic shifts in world Christianity from the West to the Global South, this book is a masterful contribution to contemporary religious history.